Eksoplaneti v naši soseščini - Poje, Urška (Matrika, 2018)
In the year 1992 the first exoplanet was discovered. Since then the number of found exoplanets has grown because of the better instruments and observation methods. From observations we can obtain many informations about new discoverd exoplanet. The most important parameters are exoplanet's radius, mass and and from these two parameters we can caculate exoplanet's density. If the exoplanet will be in the habitable zone mostly depends on distance from star to exoplanet and atmosphere compositon. In the last year scientists have discovered an exoplanet that orbits our closest star Proxima Centauri and planetary system Trappist-1, where there are seven exoplanets that orbit a red dwarf. Three exoplanets from Trappist-1 and Proxima b are candidates for planets, on which life can develop.
Keywords: astronomical observations; astronomija; astronomy; eksoplaneti; exoplanets; raziskovanje vesolja